Investigating influences on real estate agents’ ethical values: the case of real estate agents in Nigeria - Agboola, Alirat Olayinka; Ojo, Olatoye; Amidu, Abdul-Rasheed (International Journal of Strategic Property Management, 2012)
Utilizing data from questionnaire administration on a random sample of estate surveyors and valuers in real estate agency practice, this study examines the relationship between real estate agents’ demographic characteristics and their ethical values in Nigeria. Using mean rating on a 5-point Likert scale, among other findings, the study revealed that of all the ethical values examined, real estate agents approve of self-interest but disapprove of fraud in the discharge of their duties. However, the greatest evidence of disapproval of fraudulent practices is amongst female real estate agents and agents with higher levels of academic qualification. On the other hand, the study found no statistically significant relationship between the ethical values and age, year of experience and professional qualification of the respondents.First Publish Online: 2 Oct 2012